Financial innovation and monetary policy: Italy versus the United States - VACIAGO, G. (PSL Quarterly Review, 2013)
Financial innovation has been linked to the problem of monetary control in many countries. In the United States it has been suggested that high and volatile interest rates have created innovations that have reduced the effectiveness of monetary policy. There is an alternative view which believes that ineffective monetary control has created volatility in financial markets. This article considers recent developments in the Italian and United States financial system, in order to compare the evolution of innovation and its impact on monetary control. JEL: E52, E44